Periprosthetic hip infection in octogenarians: a single institution experience of 33 cases. (1st February 2023) - Karczewski, Daniel; Schönnagel, Lukas; Hipfl, Christian; Akgün, Doruk; Hardt, Sebastian
Abstract : Aims: Periprosthetic joint infection (PJI) in total hip arthroplasty in the elderly may occur but has been subject to limited investigation. This study analyzed infection characteristics, surgical outcomes, and perioperative complications of octogenarians undergoing treatment for PJI in a single university-based institution. Methods: We identified 33 patients who underwent treatment for PJIs of the hip between January 2010 and December 2019 using our institutional joint registry. Mean age was 82 years (80 to 90), with 19 females (57%) and a mean BMI of 26 kg/m 2 (17 to 41). Mean American Society of Anesthesiologists (ASA) grade was 3 (1 to 4) and mean Charlson Comorbidity Index was 6 (4 to 10). Leading pathogens included coagulase-negative Staphylococci (45%) and Enterococcus faecalis (9%). Two-stage exchange was performed in 30 joints and permanent resection arthroplasty in three. Kaplan-Meier survivorship analyses were performed. Mean follow-up was five years (3 to 7). Results: The two-year survivorship free of any recurrent PJI was 72% (95% confidence interval (CI) 56 to 89; 18 patients at risk). There were a total of nine recurrent PJIs at a mean of one year (16 days to eight years), one for the same pathogen as at index infection. One additional surgical site infection was noted at two weeks, resulting in a 69% (95% CI 52 to 86; 17 patients at risk) survivorship free of any infection at two years. There were two additional revisions for dislocations at one month each. As such, the two-year survivorship free of any revision was 61% (95% CI 42 to 80; 12 patients at risk). In addition to the aforementioned revisions, there was one additional skin grafting for a decubitus ulcer, resulting in a survivorship free of any reoperation of 54% (95% CI 35 to 73; ten patients at risk) at two years. Mean Clavien-Dindo score of perioperative complications was two out of five, with one case of perioperative death noted at six days. Conclusion: Octogenarians undergoing surgery for PJI of the hip are at low risk of acute mortality, but are at moderate risk of other perioperative complications. One in two patients will undergo a reoperation within two years, with 70% attributable to recurrent infections. Cite this article: Bone Joint J  2023;105-B(2):135–139.